Теплообменные аппараты холодильных установок - Данилова Г. Н. Галина Николаевна; Богданов С. Н. Сергей Николаевич; Иванов О. П. Олег Петрович; Медникова Н. М. Наталья Матвеевна; Гоголин А. А. Анатолий Аркадьевич (Ленинград, Машиностроение, 1973)
На обороте тит. л. авт.: